America noviter delineata. - Jansson, Jan, 1588-1664 (Ioannes Ianssonius, 1613)
Map shows known geography, settlements, ports, and coastal detail in early seventeenth century North America and South America. Includes illustrations of sea monsters, ships, and cultural observations. Insets: [Map of the Arctic Circle showing] "Groenlandi & Islandia" and [Map of the Antarctic Circle showing] "Terra Australis incognita." Relief shown pictorially. Scale not given.